Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, x^2(x^2+4)-x^2-4=0
=) x^2(x^2+4)-(x^2+4)=0
=) (x^2+4)(x^2-1)=0
=)(x^2+4)(x-1)(x+1)=0
=) x^2+4=0 =)x^2=4 =)x=2
x-1=0 =)x=1
x+1=0 =)x=-1
b,x^2-25-x-5=0
=)(x+5)(x-5)-(x+5)=0
=)(x+5)(x-6)=0
=)x+5=0 =) x=-5
x-6=0 =) x=6
x2 - 4 = 0
x2 = 4
\(\orbr{\begin{cases}x^2=2^2\\x^2=\left(-2\right)^2\end{cases}}\)
\(\orbr{\begin{cases}x=2\\x=-2\end{cases}}\)
3x2 - 75 = 0
3x2 = 75
x2 = 25
\(\orbr{\begin{cases}x^2=5^2\\x^2=\left(-5\right)^2\end{cases}}\)
\(\orbr{\begin{cases}x=5\\x=-5\end{cases}}\)
( x + 2 )2 = 25
\(\orbr{\begin{cases}\left(x+2\right)^2=5^2\\\left(x+2\right)^2=\left(-5\right)^2\end{cases}}\)
\(\orbr{\begin{cases}x+2=5\\x+2=-5\end{cases}}\)
\(\orbr{\begin{cases}x=3\\x=-7\end{cases}}\)
a, \(x^2-25-\left(x+5\right)=0\)
\(\Rightarrow x^2-5^2-\left(x+5\right)=0\)
\(\Rightarrow\left(x-5\right)\times\left(x+5\right)-\left(x+5\right)=0\)
\(\Rightarrow\left(x+5\right)\times\left(x-5-1\right)=0\)
\(\Rightarrow\left(x+5\right)\times\left(x-6\right)=0\)
\(\Rightarrow\hept{\begin{cases}x+5=0\\x-6=0\end{cases}}\)
\(\Rightarrow\hept{\begin{cases}x=0-5=\left(-5\right)\\x=0+6=6\end{cases}}\)
b, \(\left(2x-1\right)^2-\left(4x^2-1\right)=0\)
\(\Rightarrow\left(2x-1\right)^2-\left(\left(2x\right)^2-1^2\right)=0\)
\(\Rightarrow\left(2x-1\right)^2-\left(2x-1\right)\times\left(2x+1\right)=0\)
\(\Rightarrow\left(2x-1\right)\times\left(2x-1-\left(2x+1\right)\right)=0\)
\(\Rightarrow\left(2x-1\right)\times\left(2x-1-2x-1\right)=0\)
\(\Rightarrow\left(2x-1\right)\times\left(-2\right)=0\)\(\Rightarrow\left(-4x\right)+2=0\)
\(\Rightarrow\left(-4x\right)=0-2=-2\)
\(\Rightarrow x=\frac{-2}{-4}=\frac{1}{2}\)
c, \(x^2\times\left(x^2+4\right)-x^2-4=0\)
\(\Rightarrow x^2\times\left(x^2+4\right)-\left(x^2+4\right)=0\)
\(\Rightarrow\left(x^2-1\right)\times\left(x^2+4\right)=0\)
\(\Rightarrow\hept{\begin{cases}x^2-1=0\\x^2+4=0\end{cases}}\)
\(\Rightarrow\hept{\begin{cases}x^2=1\\x^2=\left(-4\right)\end{cases}}\)
\(\Rightarrow x=1\)
\(x^2-3x=0\)
\(\Leftrightarrow x\left(x-3\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=0\\x-3=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=0\\x=3\end{cases}}\)
\(x^5-9x=0\)
\(\Leftrightarrow x\left(x^4-9\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=0\\x^4-9=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=0\\x=\pm\sqrt[4]{9}\end{cases}}\)
8x2+30x+7=0
8x2+16x+14x+7=0
8x(x+2) +7(x+2)=0
(8x+7)(x+2)=0
=>\(\orbr{\begin{cases}8x+7=0\\x+2=0\end{cases}\Rightarrow\orbr{\begin{cases}x=-\frac{7}{8}\\x=-2\end{cases}}}\)
4 - 25x2 = 0
\(\Rightarrow\)25x2 = 4
\(\Rightarrow\)x2 = 4 / 25
\(\Rightarrow\)x = \(\pm\)( 2 / 5 )2